Crabs and Shrimps - Jongkar, Grinang (UNIMAS Publisher, Sarawak Forestry Corporation and Natural History Publications (Borneo) Sdn. Bhd., 2025)
The first record of a crab from the Niah limestone area dates back to 1978, when the late Lipke Bijdeley Holthuis (1921–2008), a renowned Dutch carcinologist, described Adeleana chapmani. Holthuis is known for his significant contributions to the knowledge of limestone cave crustaceans in both Gunung Mulu and Niah. A. chapmani is a semiterrestrial and troglobitic species that is strictly confined to the cave system and is endemic to the Great Cave. Compared to the limestone caves of Mulu, the crustaceans of Niah are relatively less studied. Small collections over the past 10 years have added several species of crabs and prawns to the known fauna of the limestone habitat and the streams flowing within the catchment. Currently, five species of crabs and four species of shrimps have been documented from the Niah area (see Checklist).